The Third Space Formation Of Hindu In Sidoarjo - Siti Alif Ulfah (Advanced Studies on Socio-Economy Development, 2021)
This article discusses the formation of a ‘third space’ and the articulation of Hindu cultural identity in Sidoarjo, East Java. The hegemonic discourse generally places restrictions on the articulation of religion and related issues. Notwithstanding, minority groups have tried to maintain and represent their Hindu identity. This paper addresses this issue through ethnographic research, adopting a post-colonial perspective, drawing particularly on Homi K. Bhabha’s theory of the third space (space in between). The results showed that Hindus have interpreted and articulated their cultural space through identity negotiation. In the Sidoarjo regency, there are three primary categories of Hinduism: Hinduism from Sidoarjo; Hinduism from outside Sidoarjo; and Hinduism from Bali. Despite differences between them, Hindus have worked together to develop strategies to challenge the hegemonic discourse, developing a third spatial formation that is shaped by cultural codes, social networks, educational institutions, military structure, and ogoh-ogoh. As such, the Hindus third space is productive, dynamic, and negotiatiable. Keywords: Hindu Community, Postcolonial Identity, Third Space